Penerapan Restorative Justice Dalam Penyelesaian Perkara Tindak Pidana Pencurian Di Kejaksaaan Negeri Padang - Jemmy, Marisa; Mahdianur, Mahdianur (Normative Jurnal Ilmiah Hukum, 2023)
Restorative Justice is an approach that focuses more on conditions for creating justice and balance for perpetrators of criminal acts and the victims themselves. The Padang District Prosecutor's Office has implemented Restorative Justice in 2 cases of criminal theft, namely terminating the prosecution of cases under Article 362 of the Criminal Code. The formulation of the problem in this research is: First, how is Restorative Justice implemented in resolving criminal cases of theft at the Padang District Prosecutor's Office? Second, what are the obstacles to implementing Restorative Justice in resolving criminal cases of theft at the Padang District Prosecutor's Office? Third, what are the efforts to overcome the application of Restorative Justice in resolving criminal cases of theft at the Padang District Prosecutor's Office? The method used in this research is Sociological Juridical which is descriptive in nature while the data used is primary data and secondary data as well as data collection techniques using field studies, namely library studies, interviews and observations, which are processed using editing and coding processes, then analyzed qualitatively. . The results of the research obtained are that the implementation of Restorative Justice in the Padang District Prosecutor's Office based on Prosecutor's Regulation Number 15 of 2020 has been implemented, where in this implementation the Prosecutor's Office prioritizes restorative efforts in cases of attempted theft. The obstacle in implementing Restorative Justice in resolving criminal cases of theft at the Padang District Prosecutor's Office is the fairly short time duration. Efforts to overcome the application of Restorative Justice in resolving criminal cases of theft at the Padang District Prosecutor's Office are by establishing integrity facts, improving the quality of prosecutor personnel, avoiding violations that will be committed by prosecutors in handling criminal cases through a Restorative Justice approach in accordance with the values ??espoused by the institution. social and realizing community expectations for the creation of a professional, proportional and fair law enforcement process.